Free carrier screening in coupled asymmetric GaN quantum discs - Lee, K; Na, J; Birner, S; Taylor, R; Yi, SN; Park, Y; Park, C; Kang, T (2006)
We present an investigation of free-carrier screening in coupled asymmetric GaN quantum discs with embedded AlGaN barriers using time-integrated and time-resolved micro-photoluminescence measurements, supported by three-dimensional multi-band k.p computational modeling. We observe that with increasing optical excitation the carrier lifetime decreases and emission energy blue-shifts. This originates from the screening of built-in piezo- and pyroelectric fields in the quantum discs by photo-generated free-carriers. Due to non-resonant tunneling of carriers from the smaller disc to the larger disc, free carrier screening is enhanced in the larger disc. The non-resonant tunneling was found to have a significant role in samples with a thin barrier, as the screening decreased with barrier thickness (i.e. decreased tunneling). Computational modeling, was in good agreement with the experimental results.